Fabrication and study of solar panel tracking system - Yaseen. H. Mahmood; Faris S.Atallah; Sara S .Tawfeeq (Tikrit Journal of Pure Science, 2018)
Solar energy is one of the most important task of renewable energy. Since the relative sun's motion to the Earth is variable with the seasons and from sunrise to sunset, so the energy produced by the panels is variable. To overcome this problem, we build a solar tracker that follows the sun and thus get the greatest amount of solar radiation most of the time. In this research, a solar tracking system has been manufactured locally and tested experimentally .It is found that our tracking system gives a good results in tracking the source of energy